FAKTOR YANG MEMPENGARUHI REPURCHASE INTENTION (STUDI KASUS DI PATRA JASA CONVENTION CENTER SEMARANG - Heri Prabowo; Laksono Hujianto (BBM (Buletin Bisnis & Manajemen), 2018)
The results of research by Choudury (2011) showed that service quality has a positive influence on word of mouth. Similarly penelitain by Rodney and Jhon (2009) which states that service quality affect the word of mouth. The results are different from the research by Jiewantoa et.al (2012) which states that service quality has no effect on word of mouth. Another study that states that service quality has no direct effect on word of mouth is a study by Li (2013). Li's research states that service quality has no effect on word of mouth. From the results of the above study there is a gap of research results. Furthermore, for this research to measure the influence of service quality, word of mouth and costumer perceived value to repurchase intention. In this study, as the samples are visitors Patra Jasa Convention Center Semarang a number of 150 people. The data collection tool is a statistical quantity of a statistical test with SEM using AMOS program version 18. The results show all hypothesis proposed accepted means service quality, customer perceived value, word of mouth give positive influence to repurchase intention.Keywords: service quality, customer perceived value, word of mouth, repurchase intention